Sheikh Nawawi Al-Bantani: Thoughts, Educational and Relevance to Islamic Contemporary Education - Khoirul Amin; Maragustam Siregar (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The purpose and urgency of this study are to find out the biography of Sheikh Nawawi Al-Bantani, his thoughts on conservative religion, and the relevance of his thinking on Contemporary Islamic education. Collecting data for this research is a qualitative method with a type (library research) library study. Meanwhile, in analyzing the data, researchers use content analysis. The results of this study show that Sheikh Nawawi was born in 1230 H / 1815 AD in the village of Tanara Serang Banten, and he died when he was even 84 years old. Moreover, he can be categorized as a figure from the conservative religious school (al-Mazhab al-muhafiz al-diniyya), where this school has several criteria. First, seeing that the concept of Islamic Education must be built on spiritual values. Secondly, studying and classifying science is based on religious matters. Third, the source of income is purely from the teachings of the Islamic religion. Fourth, it does not consider the concrete dynamics of the Muslim community in the classical and contemporary eras. The relevance of sheikh Nawawi's thought to contemporary Islamic Education is that Islamic Education should be built based on religion and aim to be closer to Allah Azza wa jalla and not aim to gain office, wealth, and worldliness alone.